PENGARUH STRUKTUR AKTIVA, UKURAN PERUSAHAAN, DAN LIKUIDITAS TERHADAP STRUKTUR MODAL - FAHMI, LUTHFILLAH ZUL; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This researchis meant to examine the influence of asset structure, firm size and liquidity to the capital structureof automotive companies. The population is all automotive companies which are listed in Indonesia StockExchange andthe samplesare 10 automotive companies and 5 years of observation. The data is done by usingsecondary data i.e. financial statements of automotive companies in Indonesia Stock Exchange. The hypothesistest is done by using multiple regressionsmethod. The result of the research shows that assets structure, firmsize and liquidity have significant influenceto the capital structure.Assets structure has significant and positiveinfluenceto the capital structure; this suggests that assets structure of the company have a direct influenceto thecapital structure because assets structure of the company is theassurance. The firm size has significant andpositive influenceto the capital structure, it shows that a large size companies are tend to use more debt, thus itwill increase the capital structure. And liquidity has significant and positive influenceto the capital structure; itdescribes the ability of the company to pay its short term liability by using its current assets.Keywords:Assets Structure, Firm Size, Liquidity, and Capital Structure